Extended spectrum β lactamase-producing Enterobacteriaceae shedding by race horses in Ontario, Canada - Anat Shnaiderman-Torban; Shiri Navon-Venezia; Yossi Paitan; Holly Archer; Wiessam Abu Ahmad; Darryl Bonder; Erez Hanael; Israel Nissan; Gal Zizelski Valenci; Scott J. Weese; Amir Steinman (BMC Veterinary Research, 2020)
Abstract Background We aimed to investigate the prevalence, molecular epidemiology and prevalence factors for Extended Spectrum β-Lactamase-producing Enterobacteriaceae (ESBL-E) shedding by race horses. A cross-sectional study was performed involving fecal samples collected from 169 Thoroughbred horses that were housed at a large racing facility in Ontario, Canada. Samples were enriched, plated on selective plates, sub-cultured to obtain pure cultures and ESBL production was confirmed. Bacterial species were identified and antibiotic susceptibility profiles were assessed. E. coli sequence types (ST) and ESBL genes were determined using multilocus sequence type (MLST) and sequencing. Whole genome sequencing was performed to isolates harboring CTX-M-1 gene. Medical records were reviewed and associations were investigated. Results Adult horses (n = 169), originating from 16 different barns, were sampled. ESBL-E shedding rate was 12% (n = 21/169, 95% CI 8–18%); 22 ESBL-E isolates were molecularly studied (one horse had two isolates). The main species was E. coli (91%) and the major ESBL gene was CTX-M-1 (54.5%). Ten different E. coli STs were identified. Sixty-four percent of total isolates were defined as multi-drug resistant. ESBL-E shedding horses originated from 8/16 different barns; whereas 48% (10/21) of them originated from one specific barn. Overall, antibiotic treatment in the previous month was found as a prevalence factor for ESBL-E shedding (p = 0.016, prevalence OR = 27.72, 95% CI 1.845–416.555). Conclusions Our findings demonstrate the potential diverse reservoir of ESBL-E in Thoroughbred race horses. Multi-drug resistant bacteria should be further investigated to improve antibiotic treatment regimens and equine welfare.